The Influence of Emotional Intelligence, Competence and Organizational Culture on Employee Performance PT. LAZADA Logistic - Ramdhani, Topan; Krisnandi, Herry; Digdowiseiso, Kumba (International Journal of Social Service and Research, 2024)
The purpose of writing the study is to analyze: (1) The Effect of Emotional Intelligence on Employee Performance. (2) Effect of Competence on Employee Performance. (3) The Effect of Organizational Culture on Employee Performance. This study explains both partially and simulatan, The method used in this study is a quantitative method to find out the influence between variables, where hypothesis testing uses descriptive statistical analysis and multiple linear regression analysis. The sample was 109 people. The results of this study state that there is an influence between emotional intelligence, competence, organizational culture on employee performance.